LEGAL PROTECTION OF WORKERS AND EMPLOYERS WHEN USING ARTIFICIAL INTELLIGENCE IN THE WORKING ENVIRONMENT - Živković, Antonije; Rajić Ćalić, Jovana (Serbian political thought, 2025)
The use of artificial intelligence in the work environment by both workers and employers represents the present in which many issues of labor law are realized, which indirectly affect both Commercial Law and Intellectual Property Law. In the digital age we are in, workers exercise new rights and new forms and ways of working that pose a challenge to labor legislation, while employers can use (generative) artificial intelligence tools when hiring and controlling workers, which raises a number of questions in the field of ethics, the realization of basic workers’ rights, and the protection of personal data. The issue of legal protection of artificial intelligence developed by workers in an employment relationship with an employer is open. In the spirit of the new EU regulation 2024/1689 on determining the conformity of the rules on artificial intelligence, the authors in this paper propose new legal solutions in the field of Labor Law and Intellectual Property Law (de lege ferenda).
Keywords: labor law; intellectual property law; worker; employer; artificial intelligence; new types of work